Neural stem cell transplantation improves neurological function in focal cerebral ischemia through GDNF/PI3K/AKT axis: Effect of neural stem cell transplantation on cerebral ischemia - Xu, Hongbo; Zhao, Feng; Wang, Haishuang; Liu, Qin (Cellular and Molecular Biology, 2023)
The aim of this experiment was to analyze the ameliorating effect of neural stem cells (NSCs) on focal cerebral ischemia (FCI) through GDNF/PI3K/AKT axis, so as to provide evidence for future clinical application of NSCs. In this study, the 15 Sprague-Dawley (SD) male rats were modeled for middle cerebral artery occlusion (MCAO)-induced FCI and then grouped: NSCs group was treated with NSC transplantation, GDNF/NSCs group was transplanted with recombinant adenovirus pAdEasy-1-pAdTrackCMV-GDNF-transfedcted NSCs, and the blank group was treated with normal saline transplantation. Rats were tested by rotarod and corner turn tests at 1 week and 4 weeks after NSC transplantation, and the levels of tumor necrosis factor-α (TNF-α), interleukin-6/8 (IL-6/8), superoxide dismutase (SOD) and malondialdehyde (MDA) were quantified. Then all rats were killed and their brain tissues were HE stained for the determination of and GDNF/PI3K/AKT axis-associated protein expression. The results of the experiment showed that: at the 1st and 4th week after transplantation, the time on the rod, number of turnings and SOD were the lowest in the blank group among the three groups, while IL-6, IL-8, TNF-α and MDA were the highest (P<0.05). Increased time on the rod, number of turnings and SOD, as well as decreased IL-6, IL-8, TNF-α and MDA were observed in NSCs and GDNF/NSCs groups after transplantation, with better performance in GDNF/NSCs group (P<0.05). Based on HE staining of brain tissue, GDNF/NSCs group had the most significant improvement in tissue injury and the highest GDNF, PI3K, AKT and p-AKT protein expression among the three groups (P<0.05). In conclusions, NSC transplantation can ameliorate neurological function in MCAO-induced FCI rats through the GDNF/PI3K/AKT axis.